From Box 3.3, p. 85:(adsbygoogle = window.adsbygoogle || []).push({});

Since [tex]

S^{\alpha}_{\phantom{\alpha}\beta\gamma} = S(\omega^\alpha, e_\beta, e_\gamma)

[/tex]

and

sinceS[tex]=S^{\alpha}_{\phantom{\alpha}\beta\gamma}e_\alpha\otimes\omega^\beta\otimes\omega^\gamma[/tex]

is it then true that

S[tex]=S(\omega^\alpha, e_\beta, e_\gamma)e_\alpha\otimes\omega^\beta\otimes\omega^\gamma\ ?[/tex]

Also, to get a new tensor from an old tensor, one of the techniques is to contract two of the indexes with each other. Is this another form of contraction, namely:

[tex]T_\gamma = S^{\alpha}_{\phantom{\alpha}\alpha\gamma} = S^{\alpha}_{\phantom{\alpha}\beta\gamma}\eta^{\beta}_{\phantom{\beta}\alpha} = S^{\alpha}_{\phantom{\alpha}\beta\gamma}\eta^{\beta\lambda}\eta_{\lambda\alpha}\ ?[/tex]

Finally, why is the 1^{st}term on the rhs of this equation transposed??

[tex]\nabla([/tex]R[tex]\otimes[/tex]M[tex]) = (\nabla[/tex]R[tex]\otimes[/tex]M[tex])^T\ +\ [/tex]R[tex]\otimes\nabla[/tex]M

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# GRAVITAION, by MTW, Box 3.3

**Physics Forums | Science Articles, Homework Help, Discussion**